Social media as an e-health communication channel: the use of (@medtweetmyhq) among students of UiTM Melaka / Wan Azfarozza Wan Athmar... [et al.] - Wan Athmar, Wan Azfarozza; Ghazali, Nur Azmina; Mohd Nasir, Muhammad Saiful Adli; Zuhaizar, Anis Athirah; Mohd Asli, Farahani (Universiti Teknologi MARA, Negeri Sembilan, 2018)
Social media are now acknowledged as one of the platforms for engaging e-health that contributing to serious discussion and information regarding on medical and health issues. However, there are challenges and risks associated with social media in medical and health care which is misinformation. Misinformation can spread quickly on Twitter and each retweet is exposing to wider audiences. The aim of this paper is to identify the use of @MedTweetMYHQ among its’ users sepcifically among UiTM Melaka students. The researchers used in-depth interviews to five informants based on purposive sampling. The data was analysed using thematic analysis. Four themes emerged from the analysis which are the use of @MedTweetMYHQ to receive updated useful information on health, to share information on healthy lifestyle, to debunk health myths and as a platform for health discussions